Bioactive peptides from meat industry by-products as potential antimicrobial agents based on BIOPEP-UWM database - Kęska, Paulina; Stadnik, Joanna; Kononiuk, Anna; Wójciak, Karolina (Biotechnology and Food Science, 2018)
New peptides with potential antimicrobial activity, encrypted in protein sequences of meat industry by-products were searched with bioinformatics tools using BIOPEP-UWM database. The potential of major proteins as a source of biologically active peptides with antibacterial, antiviral and antifungal activity were considered. As a result, collagen, hemoglobin, fibrinogen and selected meat tissue proteins (creatine kinase, myosin, titin) has been shown to contain short motifs responsible for antibacterial properties. The peptides with antiviral and antifungal properties were not detected.